Growth Differentiation Factor-15 Is a Predictor of Mortality in Critically Ill Patients with Sepsis. (18th October 2017) - Buendgens, Lukas; Yagmur, Eray; Bruensing, Jan; Herbers, Ulf; Baeck, Christer; Trautwein, Christian; Koch, Alexander; Tacke, Frank
Abstract : Growth differentiation factor-15 (GDF-15) is a member of the transforming growth factor- β superfamily related to inflammation and macrophage activation. Serum concentrations of GDF-15 can predict poor survival in chronic diseases, but its role in sepsis is obscure. Therefore, we investigated GDF-15 as a prognostic biomarker in critically ill patients. We measured GDF-15 levels in 219 critically ill patients (146 with sepsis, 73 without sepsis) upon admission to the intensive care unit (ICU), in comparison to 66 healthy controls. GDF-15 levels were significantly increased in ICU patients compared to controls. GDF-15 was further increased in sepsis and showed a strong association with organ dysfunction (kidney, liver and lactate) and disease severity (APACHE II and SOFA score). High GDF-15 concentrations at admission independently predicted ICU (HR 3.42; 95% CI 1.33–8.78) and overall mortality (HR 2.02, 95% CI 1.02–3.88) in all ICU critically ill patients as well as in a large subgroup of sepsis patients (ICU mortality: HR 3.16; 95% CI 1.10–9.07; overall mortality: HR 2.62; 95% CI 1.14–6.02). Collectively, serum GDF-15 levels are significantly increased in critically ill patients, associated with sepsis, organ failure, and disease severity. High GDF-15 levels at ICU admission predict short- and long-term mortality risk.